Almost Ï‰-continuous functions defined by Ï‰-open sets due to Arhangel‘ski Ì†Ä± - Rosas, E.; Carpintero, C.; Salas, M.; Sanabria, J.; Vásquez, L. (CUBO, A Mathematical Journal, 2017)
In this paper, we apply the notion of Ï‰-open sets due to Arhangel‘ski Ì†Ä± [1] to present and study a new class of functions called almost Ï‰-continuous functions. Relationships between this new class and other classes of functions are established.